PELAKSANAAN PROMOSI PADA OBJEK WISATA TAMAN PANCING ALAM MAYANG PEKANBARU - Dwitasari, Yuriche; Achmnes, Syofia; Yusrizal, Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research aimed to implementation of promotion at Taman Rekreasi Alam Mayang in Pekanbaru. This research aims : (1) to knows the goals of the promotion at Taman Rekreasi Alam Mayang in Pekanbaru, (2) to knows the reasons why the promotion must doing at Taman Rekreasi Alam Mayang in Pekanbaru, (3) to knows the promotions programs that was doing by Taman Rekreasi Alam Mayang Pekanbaru, (4) to knows who is doing the promotion at Taman Rekreasi Alam Mayang Pekanbaru, (5) to knows where is the promotion of Taman Rekreasi Alam Mayang Pekanbaru was doing.sample in this research was 100 respondent. This research uses descriptive method to clarify the issues raised in this research.the results of this research indicate that based on the research results obtained on the implementation of promotion at Taman Rekreasi Alam Mayang in Pekanbaru could be good enough. this is proved by the acquisition of overall promotion programs total score is 3,609 points.constraints in the promotion of Taman Rekreasi Alam Mayang Pekanbaru: (1) the goals of promotion is to increase the society knowledge about tourism place, to increase the number of tourist, and to increase the owner income. (2) Taman Rekreasi Alam Mayang still have problems to do the promotion programmes, such as promotion within use television and radio media. (3) Taman Rekreasi Alam Mayang Pekanbaru use the brochure to promote their information.Keyword : Promotion, Programme, Advertising, Sales Promotion, Personal Selling, Public Relations, Direct Marketing.